2020
DOI: 10.3390/genes11121518
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Warmblood Fragile Foal Syndrome Type 1 Mutation (PLOD1 c.2032G>A) in Different Horse Breeds from Europe and the United States

Abstract: Warmblood fragile foal syndrome (WFFS) is an autosomal recessive disorder caused by a single nucleotide variant in the procollagen-lysine-2-oxoglutarate-5-dioxygenase 1 gene (PLOD1:c.2032G>A, p.Gly678Arg). Homozygosity for the PLOD1 variant causes an Ehler-Danlos-like syndrome, which has to date only been reported in warmblood breeds but the WFFS allele has been also detected in the Thoroughbred. To investigate the breed distribution of the WFFS allele, 4081 horses belonging to 38 different breeds were scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 33 publications
1
28
4
Order By: Relevance
“…The frequency of the WFFS mutation in the sport horse population tested in this study (1.98%) is low in comparison to the reported frequency (11-15%) in Warmblood breeds in mainland Europe, the United States and Brazil [13,16,23] While one of the sport horse carriers in this study was reported to be of Warmblood pedigree, most sport horses tested were reported to be 'Irish Sport Horses' . The low frequency of the WFFS allele in sport horses in Ireland may be due to the influence of the traditional Irish Draught and Thoroughbred breeds on the modern Irish Sport Horse.…”
Section: Sport Horsescontrasting
confidence: 80%
See 4 more Smart Citations
“…The frequency of the WFFS mutation in the sport horse population tested in this study (1.98%) is low in comparison to the reported frequency (11-15%) in Warmblood breeds in mainland Europe, the United States and Brazil [13,16,23] While one of the sport horse carriers in this study was reported to be of Warmblood pedigree, most sport horses tested were reported to be 'Irish Sport Horses' . The low frequency of the WFFS allele in sport horses in Ireland may be due to the influence of the traditional Irish Draught and Thoroughbred breeds on the modern Irish Sport Horse.…”
Section: Sport Horsescontrasting
confidence: 80%
“…Similar carrier frequencies have been reported in Warmbloods in Europe [11,13]. More recently, a higher WFFS allele carrier frequency of 17% in the Hanoverian and Danish Warmblood breeds was described [16], while Metzger et al reported a carrier frequency of 28% in Hanoverian horses in Germany [20]. In a further study, 2.4% of Thoroughbreds in the United States (n = 716) were identified as carriers of the allele [14].…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations